The Economics of Bee Honey Production in Nineveh Province for the Production Season 2021 (NTU Journal of Agriculture and Veterinary Science, 2023)
The weakness of technical and economic knowledge of beekeepers is one of the factors affecting profit as well as the optimum production volume achieved for economic efficiency, which led to economic problems, among those problems is the decrease in the quantities supplied from bee honey production. The research aimed at studying the most important factors affecting the profit function as well as estimating the function production costs. Cross-sectional data were used in the light of a random sample that included (120) beekeepers from Nineveh Governorate. The results of estimating the profit function showed that the parameters of the function agreed with the logic of the economic theory and the statistical and standard tests. It was shown by the size of the parameters of the function that the amount of output has a great importance in profit compared with the rest of the price variables and the average production costs. As for the ratio for estimating the function of total costs, the results of the study showed that the cubic model is the most suitable for therelationship adopted in the study according to economic theory and statistical and standard tests. Depending on the cost function only, the volume achieved for the economic efficiency of honey production was obtained at the level (10,386) kg / cell. The study also showed that the technical efficiency in honey production amounted to (86%), as well as the estimation of the maximum production volume for honey in the short term, which amounted to (13.885). We infer from the study that the economic resources used in the production process were not optimally invested, which led to a decrease in production efficiency. The results of the studyrecommend working to follow production policies aimed at increasing the economic efficiency of a single cell and achieving optimal use of available resources, which is reflected in an increase in efficiency in the use of productive resources and an improvement in the efficiency of honey production.